Video as a Virtual Teacher: Analysing the Effectiveness of Digital Media-Based Flat Pattern Design Learning Towards Quality Education - Puspaneli; Puji Hujria Suci; Mimi Yupelmi; Sri Zulfia Nofrita; Ilham Zamil; Vina Oktaviani; Rafikah Husni; Reni Fitria; Hadiastuti; Hazevi Atila Yazel Aze; Yulia Aryati; Rima Agustia Utami (Jurnal Penelitian Pendidikan IPA, 2026)
This study examined the effectiveness of video tutorials in enhancing students’ cognitive understanding and psychomotor skills in Flat Pattern Design learning. A quasi-experimental pretest–posttest design was employed involving 30 fashion design students selected through purposive sampling. The instructional intervention utilized video tutorials that demonstrated each stage of the flat pattern design process, enabling students to review learning materials repeatedly and practice independently. Data were collected through cognitive achievement tests and psychomotor performance assessments and analyzed using descriptive and inferential statistics. The findings revealed statistically significant improvements in students’ learning outcomes following the intervention (p < 0.05). Cognitive achievement scores increased from pretest to posttest, accompanied by substantial gains in psychomotor performance. Classroom observations also indicated high levels of participation and engagement throughout the learning activities. These results suggest that video tutorials provide effective support for procedural learning by facilitating visual demonstration, self-paced practice, and skill mastery. The study contributes to the growing body of research on digital learning in vocational education by demonstrating the potential of video-based instruction to strengthen both conceptual understanding and practical competencies in fashion design courses